Pengaruh Susunan Dan Fraksi Volume Serat Pandan Duri Terhadap Kekuatan Tarik Sebagai Bahan Dasar Dashboard Mobil - Armannia, Vanessa Oksya; Masdani, Masdani; Husman, Husman (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The use of natural fiber-based composite materials is a key focus in reducing dependence on synthetic materials in the automotive industry. This study examines the impact of fiber volume fraction and orientation variations in Pandanus Tectorius fibers on the tensile strength of composites as an alternative material for car dashboards. These fibers were chosen for their good mechanical properties, eco-friendliness, and renewability. The composites were made using a polyester resin matrix with fiber volume fractions of 3%, 5%, and 7%, and fiber orientations of random, vertical, and horizontal. Samples were prepared using the hand lay-up method following ASTM D 638 standards. Results revealed that both fiber volume fraction and orientation significantly influenced tensile strength. The combination of vertical fiber orientation and a 7% volume fraction yielded the highest tensile strength at 38,95 MPa, while horizontal fibers with a 3% volume fraction showed the lowest at 15,35 MPa. Tensile strength increased with more fibers aligned in the tensile force direction. For comparison, ABS High Impact plastic used in dashboards has tensile strength ranging from 20 to 40 MPa. Thus, Pandanus Tectorius fiber composites meet strength requirements and present a promising eco-friendly alternative for automotive applications.